The chronology of archaeological assemblages based on an automatic Bayesian procedure: Eastern Iberia as study case. (March 2022) - Pardo-Gordó, Salvador; Aubán, Joan Bernabeu; Jiménez-Puerto, Joaquín; Armero, Carmen; García-Donato, Gonzalo
Abstract: The purpose of this work is to show an automatic Bayesian procedure to obtain accurate chronological information of archaeological assemblages characterized by palimpsest or without radiocarbon dates and whose temporal information comes only from bifacial flint arrowheads. In this paper, a classification method based on the Dirichlet-multinomial inferential process and its posterior predictive probability distribution is discussed. Its purpose is to predict the chronological period of undated archaeological assemblages (levels or sites) by means of a Bayesian predictive process based on the posterior distribution of each bifacial flint arrowhead types in the Eastern Iberia during the 4th and 3rd millennium cal. BC. The results obtained suggest that this approach is very useful to achieve an accurate chronology when other archaeological information is not available, or it is not conclusive.